THE EFFECTS OF READING INTEREST AND VOCABULARY MASTERY ON STUDENTS’ READING COMPREHENSION - Trah Kusumaningrum; Merry Lapasau (Universitas Indraprasta PGRI, 2021)
Abstract: The research aims to show that 1) there are any effects of reading interest and vocabulary mastery jointly towards students' reading comprehension, 2) there is a significant effect of reading interest towards students' reading comprehension, 3) there is a significant effect of vocabulary mastery towards students' reading comprehension. The research method is a survey with a simple random sampling for 61 students using a questionnaire used for data collection. The research results show that; 1) There are significant effects of reading interest and vocabulary mastery on students' reading comprehension. It is proved by the score of Sig 0,000 < 0,05 and F0 = 63,019. 2) There is a significant effect of reading interest on student's reading comprehension. It is proved by the score of Sig 0,011 < 0,05 and to = 2,614. 3) There is a significant effect of vocabulary mastery on student's reading comprehension. It is proven by the score of Sig 0,000 < 0,05 and to = 6,148.Keywords: reading interest, vocabulary mastery, reading comprehension